Karen Homegardens: Characteristics, Functions, and Species Diversity - Prateep Panyadee (2018)
© 2018 The New York Botanical Garden Diversity is one of the most important traits of homegardens and contributes to maintaining their functions. Here, we investigated the diversity, characteristics, and functions of 75 Karen homegardens from four villages in Chiang Mai and Tak provinces in northern Thailand. In each homegarden, all used plant species were registered and classified according to their main use. The diversity and richness in each homegarden was estimated and the stratification of plants in horizontal zones was investigated. A total 268 plant species were recorded, ranging from 100 to 146 species in each of the four villages. These plants were mostly kept in the homegarden yard or along their boundaries. The most common species were mango (Mangifera indica L.), jackfruit (Artocarpus heterophyllus Lam.), guava (Psidium guajava L.), and taro Colocasia esculenta (L.) Schott. Besides these species, most plants differed from one village to another. Distance between the homegardens was important; homegardens in the same village were more similar than those in different villages. However, beyond the individual level, the distances alone could not be used to determine similarity. Despite the variation of species found in homegardens, the function and horizontal stratification of the Karen homegardens shared many traits. They satisfied both physical and aesthetic needs to the Karen people as witnessed by the high proportion of food and ornamental species. The reverse effects of urbanization (we used the distance from the nearest urban area as a proxy) on the diversity of ornamental species was also observed. In general, Karen homegardens had high richness and diversity which directly benefited the conservation of plant species. This diversity promotes food security at the household and community levels.